2023
DOI: 10.3389/fimmu.2022.1078414
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bulk and single-cell transcriptome profiling give useful insights into the characteristics of osteoarthritis associated synovial macrophages

Abstract: BackgroundOsteoarthritis (OA) is a common chronic joint disease, but the association between molecular and cellular events and the pathogenic process of OA remains unclear.ObjectiveThe study aimed to identify key molecular and cellular events in the processes of immune infiltration of the synovium in OA and to provide potential diagnostic and therapeutic targets.MethodsTo identify the common differential expression genes and function analysis in OA, we compared the expression between normal and OA samples and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…[ 28 ] Therefore, reducing synovitis may be an effective way to delay cartilage degeneration, and macrophages are the best diagnostic markers for immune infiltration of bone and joint synovitis. [ 29 ] To quickly and accurately understand the current research situation and future trends, we use bibliometrics to analyze the papers from 2009 to 2022, providing reference data for researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] Therefore, reducing synovitis may be an effective way to delay cartilage degeneration, and macrophages are the best diagnostic markers for immune infiltration of bone and joint synovitis. [ 29 ] To quickly and accurately understand the current research situation and future trends, we use bibliometrics to analyze the papers from 2009 to 2022, providing reference data for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…[37] It has been reported that both immune system processes and inflammation play roles in the progression of OA. Through KEGG analysis, Liao et al [29] learned that differentially expressed genes in OA synovium are mainly involved in immune-related pathways such as the TNF signaling pathway, NF-KB signaling pathway, MAPK signaling pathway, and T-cell receptor signaling pathway. As indicative of the current research situation, our screening results also found that the "T cells" in Cluster 2 are one of the most frequently used keywords.…”
Section: Introductionmentioning
confidence: 99%
“…), scientists reported the M1 macrophages increasing in synovium and synovia even before the cartilage degradation (Sun, Panchal, et al, 2017). Another differentially expressed and gene screening study reports that cells including M2 macrophage and memory B cell, as well as CCL signaling pathways (which have the greatest communication between macrophage and T cells), are significantly associated with OA (Liao et al, 2022). However, it is worth knowing that the expression of CD40 has been demonstrated not highly correlated with OA but with RA in an early study (Gotoh et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Gene set variation analysis (GSVA) were used to estimate the relative enrichment of a gene set of interest over a sample population, which is used to observe the variation in the activity of a set of genes corresponding to a particular biological process [ 15 ]. Followed by previous study [ 16 ], the GSVA R package [ 17 ] was used to analyze the pathway between two different groups of samples, and the defined gene set: HALLMARKS was downloaded from the Molecular Signature Database. “zscore” algorithm was used to give score to each sample and used this enrichment score to represent the degree of absolute enrichment of a gene set hallmark, while different scores also represent the activity degree of the hallmarks in the sample.…”
Section: Methodsmentioning
confidence: 99%